The effect of fermented duckweed (Lemna minor) in feed on growth and nutritional quality of tilapia (Oreochromis niloticus) - Vivi Endar Herawati; PINANDOYO PINANDOYO; Y.S. DARMANTO; NURMANITA RISMANINGSIH; SETO WINDARTO; OCKY KARNA RADJASA (Society for Indonesian Biodiversity, 2020)
Abstract. Herawati VE, Pinandoyo, Darmanto YS, Rismaningsih N, Widarto S, Radjasa OK. 2020. The effect of fermented duckweed (Lemna minor) in feed on growth and nutritional quality of tilapia (Oreochromis niloticus). Biodiversitas 21: 3350-3358. One of the raw materials used for making tilapia fish feed is soybean meal. Soybean prices continue to rise and currently reach 4,500 rupiah/kg, so that alternative feed ingredients that are cheap and environmentally friendly need to be sought. Alternative feed ingredients that can be utilized in making feed, one of which is Lemna minor meal. Duckweed (Lemna minor) which has a high nutrient content, such as 23.47% crude protein, 3.99% crude fat, 29.92% crude fiber, 23.6% ash, and 19.02% nitrogen-free extract, will be the best candidate as an alternative feed ingredient. This study aims to find growth performance and nutritional quality of tilapia fed by different feed formulations using different amounts of fermented L. minor meal. The dosage treatments of feed with fermented L. minor meal are 0% (A), 2.5% (B), 5% (C), and 7.5% (D). Feeding of tilapia using fermented L. minor meal has a significant effect (P<0.05) on total feed consumption, feed utilization efficiency, protein efficiency ratio, and relative growth rate, and had no significant effect (P>0.05) on survival rate. The results found that the best biomass weight, total feed consumption, feed utilization efficiency, relative growth rate, protein efficiency ratio, and survival rate value was in the treatment B (usage of 2.5 % L. minor meal) which were 38.58g, 110.17g, 70.10%, 2.01%, 1.98%, and 94.44%, respectively. The best nutritional quality was in the treatment B (usage of 2.5 % L. minor meal) which was amino acid lysine, the highest value of amino acid lysine was 25.22% and the highest value of linoleic fatty acid was 4.37%.